Under a New Light: Regulation of Light-Dependent Pathways by Non-coding RNAs - Sánchez-Retuerta, Camila; Suaréz-López, Paula; Henriques, Rossana (Frontiers in Plant Science, 2018)
The biological relevance of non-protein coding RNAs in the regulation of critical plant processes has been firmly established in recent years. This has been mostly achieved with the discovery and functional characterisation of small non-coding RNAs, such as small interfering RNAs (siRNAs) and microRNAs (miRNAs). However, recent next-generation sequencing techniques have widened our view of the non-coding RNA world, which now includes long non-coding RNAs (lncRNAs). Small and lncRNAs seem to diverge in their biogenesis and mode of action, but growing evidence highlights their relevance in developmental processes and in responses to particular environmental conditions. Light can affect MIRNA gene transcription, miRNA biogenesis and RNA-induced silencing complex (RISC) activity, thus controlling not only miRNA accumulation but also their biological function. In addition, miRNAs can mediate several light-regulated processes. On the lncRNA world, few reports are available, but they already indicate a role in the regulation of photomorphogenesis, cotyledon greening and photoperiod-regulated flowering. In this review, we will discuss how light controls MIRNA gene expression and the accumulation of their mature forms, with a particular emphasis on those miRNAs that respond to different light qualities and are conserved among species. We will also address the role of small non-coding RNAs, particularly miRNAs, and lncRNAs in the regulation of light-dependent pathways. We will mainly focus on the recent progress done in understanding the interconnection between these non-coding RNAs and photomorphogenesis, circadian clock function and photoperiod-dependent flowering.